The Analysis of Problem Solving Ability in Natural Sciences and Life Skills through Guided Discovery Learning in the View of Student Learning Independence in the Subject Matter of Changes in Energy Forms - Mahdi; Tri Joko Raharjo; Widiasih (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study was to examine the effect of guided discovery learning on science problem solving ability and life skills in terms of student learning independence in the form of energy in grade IV elementary school. Method: The research design used quasi experiment with factorial design. The research sample was 50 fourth grade students from 2 elementary schools. Participants were tested using a problem solving ability test with essay form (pretest and posttest) and student life skills data using observation sheets. Data were analyzed by one way manova test followed by BNT test. Results: The guided discovery learning method (M = 67.8; SD = 14.0) had significantly better problem solving ability than the conventional learning method (M = 57.8; SD = 13.6), [F (5; 44) = 10.53, p = 0.000, Î·p2 = 0.55]. The guided discovery learning method (M = 74.9; SD = 10.9) had significantly better life skills than the conventional learning method (M = 65.3; SD = 9.2); [F (5; 44) = 40,49, p = 0.000, Î·p2 = 0.821].